Enhancing the Performance of DFIG Wind Turbines Considering Excitation Parameters of the Insulated Gate Bipolar Transistors and a New PLL Scheme - Okedu, Kenneth E.; Barghash, Hind F. A. (Frontiers in Energy Research, 2021)
The major aim for achieving the successful synchronization of a wind turbine system to the grid is to mitigate electrical and mechanical stresses on the wind generator. During transient state, the gearbox, shaft, and rotor of the wind generator could be damaged due to mechanical stress. The rotor and stator windings of the wind generator, including its insulation, could be affected. This paper undertakes an extensive analysis of the effects of the excitation parameters of the power converter Insulated Gate Bipolar Transistors (IGBTs), on the transient state performance of the Doubly Fed Induction Generator (DFIG), considering different scenarios. The optimal excitation parameters of IGBTs were used for further analysis of the wind generator, considering a new Phase-Locked-Loop (PLL) scheme. The PLL computes the phase displacement of the grid required to achieve orientation and synchronization control. Consequently, it helps in preventing power system distortion due to stator-grid interphase. This paper proposes a new approach that integrates PLL control strategy and a Series Dynamic Braking Resistor (SDBR) to augment the fault ride through capability of a variable speed wind turbine that is DFIG-based. The SDBR helps the post fault recovery of the wind generator. Simulations were run in Power System Computer Aided Design and Electromagnetic Transient state Including DC (PSCAD/EMTDC) to examine severe fault conditions, and to test the robustness of the controllers employed. The results show that the proposed hybrid control strategy aids the fast recovery of the DFIG wind generator variables during fault conditions.